Upaya Perlindungan Hukum Bagi Pelaku Usaha yang Dirugikan Akibat Adanya Ulasan Negatif Fiktif Ditinjau dari Fatwa DSN MUI No 24 Tahun 2017 (Studi Kasus Pada Aplikasi Google Maps) - Adelia Budiman Budiman; Iwan Iwan (LPPM Universitas Ekasakti Padang, 2023)
This study examines the impact and legal protection provided to businesses facing fictitious negative reviews on the Google Maps application based on the guidelines recommended by the Fatwa DSN MUI No. 24 of 2017. The research aims to understand how fictitious negative reviews on the Google Maps application affect businesses and to evaluate the extent to which the fatwa has been implemented in protecting the rights and reputation of affected businesses. Additionally, it seeks to identify effective legal protection measures for businesses. The research utilizes a qualitative method with a case study approach, allowing for an in-depth understanding of real cases experienced by businesses suffering losses due to fictitious negative reviews on Google Maps. The research findings indicate that Fatwa DSN MUI No. 24 of 2017 plays a crucial role in providing legal protection guidelines for businesses affected by fictitious negative reviews. The impacts include decreased revenue, damaged reputation, and financial losses. Therefore, the study provides recommendations for protecting against fictitious negative reviews, including through legal approaches and reputation management. In conclusion, this fatwa holds significant relevance in legal protection and maintaining the reputation of businesses in the digital era.